COMPARISON OF PHYTOPLANKTON ABUNDANCE BETWEEN MANGROVE WATERS AND OPEN WATERS IN MENGKAPAN VILLAGE SUNGAI APIT DISTRICT SIAK REGENCY RIAU PROVINCE - Budi Kurniayawan; Adriman Adriman; Eni Sumarsih (Berkala Perikanan Terubuk, 2022)
Phytoplankton is a organisms with characteristic  as primary producers and bioindicator of marin and fresh waters.  Mangrove waters and open waters generally have different characteristics of ecosystem and organism that live in these waters. The research aim to determine the difference of phytoplankton in mangrove waters and open waters including diversity, uniformity, and dominance of two type of waters. This research was conducted in Desember 2020. The sampling locations take out  in two sampling areas which are mangrove waters and open waters in th Mengkapan Village, Sungai Apit District, Siak Regency. Data identifications and analysis carried out in aquatic  ecology laboratory of  Faculty of Fisheries and Marine Science, University Riau. The comparison of the data of phytoplankton abundance uses the PAST application and Microsoft Excel (T-Test). The range of abundance of phytoplankton in Mengkapan Village waters is between 576-856 sel/L with Bacillariophyceae as the dominant class. There is no significant difference between the two waters, but the water Mengkapan Village has low water quality and influences the phytoplankton abundance